The Southampton Consensus Guidelines for Laparoscopic Liver Surgery: From Indication to Implementation. Issue 1 (July 2018) - Abu Hilal, Mohammad; Aldrighetti, Luca; Dagher, Ibrahim; Edwin, Bjorn; Troisi, Roberto Ivan; Alikhanov, Ruslan; Aroori, Somaiah; Belli, Giulio; Besselink, Marc; Briceno, Javier; Gayet, Brice; D'Hondt, Mathieu; et al.
Abstract : Objective: The European Guidelines Meeting on Laparoscopic Liver Surgery was held in Southampton on February 10 and 11, 2017 with the aim of presenting and validating clinical practice guidelines for laparoscopic liver surgery. Background: The exponential growth of laparoscopic liver surgery in recent years mandates the development of clinical practice guidelines to direct the speciality's continued safe progression and dissemination. Methods: A unique approach to the development of clinical guidelines was adopted. Three well-validated methods were integrated: the Scottish Intercollegiate Guidelines Network methodology for the assessment of evidence and development of guideline statements; the Delphi method of establishing expert consensus, and the AGREE II-GRS Instrument for the assessment of the methodological quality and external validation of the final statements. Results: Along with the committee chairman, 22 European experts; 7 junior experts and an independent validation committee of 11 international surgeons produced 67 guideline statements for the safe progression and dissemination of laparoscopic liver surgery. Each of the statements reached at least a 95% consensus among the experts and were endorsed by the independent validation committee. Conclusion: The European Guidelines Meeting for Laparoscopic Liver Surgery has produced a set of clinical practice guidelines that have been independently validated for the safe development and progression of laparoscopic liver surgery. The Southampton Guidelines have amalgamated the available evidence and a wealth of experts' knowledge taking in consideration the relevant stakeholders' opinions and complying with the international methodology standards. Abstract : Supplemental Digital Content is available in the text